Epidemiological analysis of leprosy per sex in the state of Paraíba (Research, Society and Development, 2020)
Introduction: Leprosy holds itself as a public health care issue, of high transcendence, due to its high disabling potential. Studying this disease per sex is relevant, because it allows the indication of access differences regarding the programs, and the population’s ability to access public health care services. Objectives: This research’s objective was to analyze leprosy’s clinical and epidemiological aspects, per sex, in the state of Paraíba from 2008 to 2017. Methods: This is a documentary, descriptive, time series research with a quantitative approach. The sample consisted of new leprosy cases extracted from the Brazilian Notification Grievance Information System. A descriptive analysis of the data and the Pearson chi-square test were used to analyze the association between leprosy’s clinical variables and different sexes. Results: 6.271 newly diagnosed leprosy cases were analyzed, with higher incidence amongst male individuals. Leprosy affects both sexes, however, when compared to women, men develop the disease’s most severe forms; multibacillary leprosy (66.79%), dimorphic clinical classification (36.14%) and grade 2 physical disabilities (11.66%) (p